Elaboration and validation of an algorithm for treating peripheral intravenous infiltration and extravasation in children - Luciano Marques dos Santos; Katharinne de Jesus Nunes; Cleonara Sousa Gomes e Silva; Denise Miyuki Kusahara; Elisa da Conceição Rodrigues; Ariane Ferreira Machado Avelar (Universidade de São Paulo, 2021)
Objective: to elaborate and validate the content and appearance of an algorithm for treating infiltration and extravasation of non-chemotherapy drugs and solutions administered to children. Method: a methodological study of the technology formulation and validation type. To elaborate the algorithm, a bibliographic review was carried out to list the scientific evidence on the treatment of infiltration and extravasation. Content and appearance validation was in charge of 14 specialists in pediatric nursing, using the Delphi technique, adopting a value equal to or greater than 0.80 as Content Validation Index. Results: the algorithm was validated in the third evaluation by the judges, reaching a Global Content Validation Index of 0.99, being composed by the perception of the occurrence of the complication; discontinuation of intravenous therapy infusion; verification of signs and symptoms; measurement of edema; application of an infiltration and extravasation assessment scale and conduits to be used according to the characteristics of the fluid administered and the type of complication. Conclusion: the algorithm was validated and can be used in a practical and objective way by health professionals, in order to promote safety in the care of hospitalized children, with regard to reducing harms caused by infiltration and extravasation.